2016
DOI: 10.1177/0363546516651831
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Repair Tension in Arthroscopic Rotator Cuff Repair

Abstract: Our intraoperative model for the estimation of rotator cuff repair tension showed an inverse correlation of repair tension with healing at the repair site, suggesting that complete healing is less likely with high-tension repairs. A significant association was observed on MRI between a high level of FD of the infraspinatus and repaired tendon integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 41 publications
0
40
0
Order By: Relevance
“…It is generally accepted that the excessive tension on the repaired footprint site is responsible for the high retear rate. 4) Kim et al 4) showed that the tear size and tension at the repaired site were inversely correlated with healing. This also can be applied to irreparable rotator cuff tears that constitute up to 30% of all rotator cuff tears.…”
mentioning
confidence: 99%
“…It is generally accepted that the excessive tension on the repaired footprint site is responsible for the high retear rate. 4) Kim et al 4) showed that the tear size and tension at the repaired site were inversely correlated with healing. This also can be applied to irreparable rotator cuff tears that constitute up to 30% of all rotator cuff tears.…”
mentioning
confidence: 99%
“…Correlation between tear size and repair tension, which affects healing of repair site, has been reported. 40 However, detailed distribution of mechanical stress in the muscle after tendon repair remains unelucidated. Muscle fiber tension could be associated with size of tear and adaptation of muscle sarcomere length after injury.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative measurements of the tensile strength 6,15,19,20 and tetanic contraction by electrical stimulation 1,9,12,14,25,27 have been proposed to determine the residual contractility of a long-standing torn rotator cuff muscle. These methods require special equipment and additional operative time for measurement.…”
Section: Discussionmentioning
confidence: 99%
“…In the restoration of shoulder abduction function, decreased contractility of the torn rotator cuff muscle may be a cause of a poor result. 1,6,9,12,14,15,19,20,25,27 Hersche and Gerber 19 reported that increased passive tension of the supraspinatus was observed in cases with long-standing tendon rupture.…”
mentioning
confidence: 99%